Percentage depth dose fragmentation for investigating and assessing the photon beam dosimetry quality. Issue 3 (4th December 2018) - Bencheikh, Mohamed; Maghnouj, Abdelmajid; Tajmouati, Jaouad
Abstract: Aim: The purpose of this study is to introduce a new approach to assess the dosimetry quality of photon beam with energy and irradiation field size. This approach is based on percentage depth dose (PDD) fragmentation for investigating the dosimetry quality. Materials and methods: For the investigation of the dosimetry quality of 6 and 18 MV photon beams, we have proceeded to fragment the PDD at different field sizes. This approach checks the overall PDD and is not restricted to the exponential decay regions, as per the International Atomic Energy Agency Technical Reports Series No 398 and the American Association of Physicist in Medicine Task Group 51 recommendations. Results and discussion: The 6 MV photon beam deposited more energy in the target volume than the 18 MV photon beam. The dose delivered by the 6 MV beam is greater by a factor of 1·5 than that delivered by the 18 MV beam in the build-up region and the dose delivered by the 6 MV beam is greater by a factor of 2·6 than that delivered by the 18 MV beam in the electronic equilibrium and the exponential decay regions. Conclusion: The dose measured at different points of the beam is higher for 6 MV than for 18 MV photon beam. Therefore, the 6 MV beam is more dosimetrically efficient than the 18 MV beam. Using the proposed approach, we can assess the dosimetry quality by taking into account overall PDD not only in the exponential decay region but also in the field.